Evaluation of operating conditions of cargo transportation by cabotage in Brazil: A multicriteria approach from the shipowners’ point of view (Research, Society and Development, 2021)
The purpose of this study was to develop and apply a model to evaluate the operating conditions of cargo transportation by cabotage in Brazil, from the perspective of Brazilian shipping companies operating in this segment. The evaluation model was developed based on the Multicriteria Decision Aid (MCDA) methodology, conceived under the constructivist paradigm and with the participation of a team of experts in cabotage, who built a framework for evaluation of this transportation mode. The global evaluation of the conditions of cargo transportation by cabotage in Brazil, based on this framework, was scored 3.9, - on a scale of zero to ten, - a score considered extremely low for a segment of cargo transportation so important and with such weight to the Brazilian economy. It was concluded that this score reflects the situation of shortage, neglect, and abandonment currently faced by shipping companies that offer cargo transportation services along the Brazilian coast. This work contributes to the construction of a multicriteria evaluation model, which can be replicated for other modes of transportation, with the necessary adjustments.